INCOME CONTRIBUTION TOWARDS THE WELFARE OF RICE FARMING HOUSEHOLDS - Managanta, Andri Amaliel; Lustari, Shinta; Tanari, Yulinda (Universitas Sintuwu Maroso, 2025)
Rice is the main staple food of the people in Indonesia, so rice production has a strategic role in national food security. In Central Sulawesi, the agricultural sector, especially rice farming, is the main source of income for most households. This study aims to analyze the amount of income obtained by farmers from rice farming and its contribution to the level of welfare of farmer households. The population was carried out in Sawidago Village North Pamona District Poso Regency Central Sulawesi Province. The study population consisted of 453 farmers who joined 11 farmer groups, and 81 farmers were selected as samples. The results showed that the average income of lowland rice farmers per planting season was IDR 2,255,291 or equivalent to IDR 576,322 per month, which is below the Poso Regency Minimum Wage of IDR 2,586,036 per month. Nevertheless, rice farming made a large contribution to the total income of farmer households, namely 61%. The level of welfare of farming households, measured by indicators such as population, education, employment, household consumption or expenditure patterns, housing, and social environment, indicates that the majority of farmers are in the prosperous category. The results of this study indicate that although income from rice farming is relatively low, its contribution to household income structure is quite significant. Therefore, an active role for farmers is needed to improve their family's welfare.